Bluetooth-based Heart Rate and Oxygen Saturation Monitoring System HC-05 Based on IoT - Afandy, Moh .; Rianto, Muhammad Ikbal; Putra P, Muhammad Farhan (Jambura Journal of Electrical and Electronics Engineering, 2025)
The purpose of this study was to design a heart rate and oxygen saturation measuring device using the reflectance method that is in accordance with standardized devices and connected to the application via a Bluetooth connection with a reporting system for measurement results that have abnormal heart performance. This study uses a design method with the use of the Max30100 sensor as the main component of this device. Based on the results of testing the sensor components of the device in testing the level of heart performance in the form of heart rate and oxygen saturation with the reflectance method in testing with a comparative device in the form of a fingertip pulse oximeter, an average error percentage of 1.73% and a measurement accuracy of 98.38% was obtained. Testing with a similar comparative device was carried out by the Smart Y68, an average error percentage of 1.73% and a measurement accuracy of 98.27%. As for testing the device with respondents, the results showed that 2/5 of the samples had a healthy heart performance level but required attention to their heart rate, namely samples A2 and A4. The design embedded a location reporting system from the use of the remote system application. The location tracking results obtained an error value of 0.002192% with an average percentage error in latitude of 0.0043% and an average percentage error in longitude of 0.000084%.Tujuan penelitian ini merancang alat pengukur detak jantung dan saturasi oksigen menggunakan metode reflectance yang sesuai dengan alat yang terstandarisasi dan terhubung pada aplikasi melalui koneksi bluetooth dengan adanya sistem pelaporan terhadap hasil pengukuran yang memiliki kinerja jantung yang abnormal. Penelitian ini menggunakan menggunakan metode rancang bangun dengan penggunaan sensor Max30100 sebagai komponen utama pada alat ini. Berdasarkan hasil pengujian komponen sensor alat dalam pengujian tingkat kinerja jantung berupa detak jantung dan saturasi oksigen dengan metode reflectance pada pengujian dengan alat pembanding berupa pulse oxymeter fingertip didapatkan rerata persentase error sebesar 1,73% dan akurasi pengukuran sebesar 98,38%. Pengujian dengan alat pembanding serupa dilakukan Smart Y68 didapatkan rata-rata persetanse error 1,73% dan akurasi pengukuran sebesar 98,27%. Adapun pengujian alat dengan responden didapatkan hasil bahwa dari 2/5 dari sampel memiliki tingkat kinerja jantung yang sehat tapi memerlukan perhatian pada detak jantung, yaitu sampel A2 dan A4. Dalam rancangan disematkan sematkan sistem pelaporan lokasi dari penggunaan aplikasi sistem jarak jauh. Hasil pelacakan lokasi didapatkan nilai error sebesar 0,002192% dengan rata-rata persentase error pada latitude sebesar 0,0043% dan rata-rata persentase error pada longitude sebesar 0,000084%.